The silent storm within a young woman’s journey through hormonal havoc - Sourav, Md. Rakibur Rahman; Zannat, Tanjina; Sarker, Md Mohiuddin; Hasan, Md. Mahmud; Banna, Anaya Saha; Sarker, Soma (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 32-year-old female presented with progressive weight gain, hirsutism, and generalized hyperpigmentation. She reported irregular menstruation followed by amenorrhea for two years, recurrent dull frontal headaches with visual disturbance, and episodes of convulsion. She also experienced back pain, a gradual loss of height, and proximal muscle weakness. History revealed diabetes for 7 years, hypertension for 4 years, and homeopathic medicine use for 1 year. On examination, she was obese (BMI 27 kg/m²) with cushingoid features: a rounded plethoric face, a dorsocervical fat pad, supraclavicular fullness, truncal obesity, purple striae, thin bruised skin, and acne. Hirsutism was moderate (Ferriman-Gallwey score 17). Generalized hyperpigmentation, including the oral mucosa, was evident. Neurological examination revealed a right temporal visual field defect and proximal limb weakness (MRC 3/5). Musculoskeletal evaluation showed positive Gowers’ sign, low MMT-8 score, and thoracic kyphosis. Biochemical evaluation confirmed hypercortisolism with elevated ACTH. Pituitary MRI revealed an adenoma, but HDDST was not suppressed. Right lateralization during IPSS confirmed a diagnosis of Cushing’s disease due to pituitary adenoma. She underwent transsphenoidal pituitary surgery, after which pigmentation regressed and weight declined. Postoperatively, she was managed with hydrocortisone, antiepileptics, metformin, antihypertensive, and supportive therapy. Long-term follow-up was planned with biochemical surveillance and bone health monitoring. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S72]